En bloc resection of urothelium carcinoma of the bladder (EBRUC): a European multicenter study to compare safety, efficacy, and outcome of laser and electrical en bloc transurethral resection of bladder tumor - Kramer, Mario Wolfgang; Rassweiler, Jens; Klein, Jan (World journal of urology, 2015)
PurposeEn bloc resection of bladder tumors (ERBT) may improve staging quality and perioperative morbidity and influence tumor recurrence. This study was designed to evaluate the safety, efficacy, and recurrence rates of electrical versus laser en bloc resection of bladder tumors.MethodsThis European multicenter study included 221 patients at six academic hospitals. Transurethral ERBT was performed with monopolar/bipolar current or holmium/thulium laser energy. Staging quality measured by detrusor muscle involvement, various perioperative parameters, and 12-month follow-up data was analyzed.ResultsElectrical and laser ERBT were used to treat 156 and 65 patients, respectively. Median tumor size was 2.1 cm; largest tumor was 5 cm. Detrusor muscle was present in 97.3 %. A switch to conventional TURBT was significantly more frequent in the electrical ERBT group (26.3 vs. 1.5 %, p < 0.001). Median operation duration (25 min), postoperative irrigation (1 day), catheterization time (2 days), and hospitalization (3 days) were similar. Overall complication rate was low (Clavien ≥ 3, n = 6 [2.7 %]). Hemoglobin was significantly lower after electrical ERBT (p = 0.0013); however, overall hemoglobin loss was not clinically relevant (0.38 g/dl). Patients (n = 148) were followed for 12 months; 33 (22.3 %) had recurrences. In total, 63.6 % recurrences occurred outside the ERBT resection field. No difference was noted between ERBT groups.ConclusionsERBT is safe and reliable regardless of the energy source and provides high-quality resections of tumors >1 cm. Recurrence rates did not differ between groups, and the majority of recurrences occurred outside the ERBT resection field.